Структура професійної соціалізації студентів інженерних спеціальностей - Мовчан, Яна Олександрівна (Національний університет оборони України імені Івана Черняховського, 2015)
У статті подано обґрунтування структури професійної соціалізації студентів інженерних спеціальностей. Запропоновано досліджувати процес професійної соціалізації у контексті запропонованих компонентів та їх показників.

The article gives the ground of professional socialization's structure of students majoring in engineering. It is analyzed demands for future engineers in psychological aspect. The need is stressed to design the structure of professional socialization of students major in engineering. It is reported that effectiveness of learning depends on a lot of factors. It is dealt with professional formation of future engineer like competitive specialist. It is marked out the socialization and professional socialization factors. It is considered the engineer's activity and functions which he carries out. It is emphasized professional and personal qualities which characterize а modern engineer. It is highlighted the importance of professional self-determination. Also it is emphasized a professional identity like important constituent of students' professional socialization. It is presented the definition of student’s professional socialization. Thereupon it is extracted three components (social and adaptive one, motivational and value one, professional and reflexive one) and their attributes. Within the framework of these components it is offered to investigate the process of professional socialization of students majoring in engineering.
Professional socialisation's structure of students majoring in engineering
Keywords: навчальний процес; вища технічна школа; освіта; психологія; фактори професійного самовизначення; мотивація; professional socialization; students; engineer